2014
DOI: 10.1590/bjpt-rbf.2014.0048
|View full text |Cite
|
Sign up to set email alerts
|

Breathing exercises: influence on breathing patterns and thoracoabdominal motion in healthy subjects

Abstract: BACKGROUND: The mechanisms underlying breathing exercises have not been fully elucidated. OBJECTIVES: To evaluate the impact of four on breathing exercises (diaphragmatic breathing, inspiratory sighs, sustained maximal inspiration and intercostal exercise) the on breathing pattern and thoracoabdominal motion in healthy subjects. METHOD: Fifteen subjects of both sexes, aged 23±1.5 years old and with normal pulmonary function tests, participated in the study. The subjects were evaluated using the optoelectronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 22 publications
1
25
0
3
Order By: Relevance
“…With regard to the asynchrony, the present study showed no differences in phase angle among conditions, but significant increases in the inspiratory phase ratio and expiratory phase ratio were found during diaphragmatic breathing and diaphragmatic breathing plus pursed-lips breathing compared with quiet breathing. This finding corroborated reports of some studies of subjects with COPD that found increases in asynchrony during diaphragmatic breathing, 10,13,29,30 which seem to be related to (1) the sitting position assumed for the evaluation (a higher trunk elevation favors greater asynchrony in subjects with COPD), 29 (2) the voluntary changes in the breathing pattern assumed during the breathing exercises (even for healthy subjects, the spontaneous breathing pattern presents asynchrony), 38 and (3) the greater focus on the use of the diaphragm (according to the instructions for diaphragmatic breathing and diaphragmatic breathing plus pursed-lips breath-ing) performed by subjects with biomechanical impairment of this muscle when considering that they have a respiratory overload while performing any type of exercise. 30,39 Both breathing exercises promoted a decrease in the breathing frequency due to the increase of inspiratory time and expiratory time.…”
Section: Discussionsupporting
confidence: 89%
“…With regard to the asynchrony, the present study showed no differences in phase angle among conditions, but significant increases in the inspiratory phase ratio and expiratory phase ratio were found during diaphragmatic breathing and diaphragmatic breathing plus pursed-lips breathing compared with quiet breathing. This finding corroborated reports of some studies of subjects with COPD that found increases in asynchrony during diaphragmatic breathing, 10,13,29,30 which seem to be related to (1) the sitting position assumed for the evaluation (a higher trunk elevation favors greater asynchrony in subjects with COPD), 29 (2) the voluntary changes in the breathing pattern assumed during the breathing exercises (even for healthy subjects, the spontaneous breathing pattern presents asynchrony), 38 and (3) the greater focus on the use of the diaphragm (according to the instructions for diaphragmatic breathing and diaphragmatic breathing plus pursed-lips breath-ing) performed by subjects with biomechanical impairment of this muscle when considering that they have a respiratory overload while performing any type of exercise. 30,39 Both breathing exercises promoted a decrease in the breathing frequency due to the increase of inspiratory time and expiratory time.…”
Section: Discussionsupporting
confidence: 89%
“…This technique promotes further displacement of the abdominal muscles. We also taught the sustained maximal inspiration technique, with the aim to increase lung volume and improve gas exchange (Hinkle & Cheever, ; Vieira et al., ). Breathing techniques together with cough enhancement contribute to maintain the airway patency and a satisfactory ventilation‐perfusion ratio.…”
Section: Discussionmentioning
confidence: 99%
“…A period of 5 to 10 minutes of training was established so that patients could adapt to the pattern. Success was assessed visually, and the execution of the pattern was considered satisfactory when there was a clear visualization of the increase in abdominal volume during inspiration [14]. After training the diaphragmatic breathing pattern, the individual was asked to quickly inhale moving the abdomen outward in a ballistic manner to familiarize himself with the speed and strength to be performed during the sniff maneuvers.…”
Section: Methodsmentioning
confidence: 99%